PENGARUH EASE OF USE, USEFULNESS DAN SOCIAL INFLUENCE TERHADAP INTENSI MENGGUNAKAN DOMPET DIGITAL - Muhammad Fahmi Bahar (Jurnal Nusa Manajemen, 2025)
This study aims to analyze the factors that influence the intention of generation Z to use digital wallets as a form of adoption of non-cash payment technology in Indonesia. With a quantitative approach and survey methodology using a questionnaire, this study examines the effect of the variables ease of use, usefulness, and social influence on the intention to use digital wallets. The results of the analysis show that the variables ease of use and social influence have a significant effect on the intention to use, while usefulness does not show a significant effect. This finding confirms that the factors of ease and social influence are the main drivers in the process of adopting digital financial technology among the younger generation of Indonesia. The practical implications of the results of this study provide guidance for technology developers and industry players in designing effective marketing strategies, as well as supporting the development of theories in the field of technology adoption, especially in the context of Indonesia in the digital era.